Molecular mechanisms in spindle positioning: structures and new concepts - Stevermann, Lea; Liakopoulos, Dimitris (Current opinion in cell biology, 2012)
Coordination of cell cleavage with respect to cell geometry, cell polarity and neighboring tissues is critical for tissue maintenance, malignant transformation and metastasis. The position of the mitotic spindle within the cell determines where cell cleavage occurs. Spindle positioning is often mediated through capture of astral microtubules by motor proteins at the cell cortex. Recently, the core dynein anchor complex has been structurally resolved. Junctional complexes were shown to provide additional capture sites for astral microtubules in proliferating tissues. Finally, latest studies show that signals from centrosomes control spindle positioning and propose novel concepts for generation of centrosome identity.
Gesehen am 17:04.2018